2006
DOI: 10.1017/s0950268806007023
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility and genetic characteristics ofHaemophilus influenzaeisolated from patients with respiratory tract infections between 1987 and 2000, including β-lactamase-negative ampicillin-resistant strains

Abstract: SUMMARYThe minimum inhibitory concentration (MIC) of five antibiotics and the presence of resistance genes was determined in 163Haemophilus influenzaeisolates collected over 13 years (1987–2000) in four two-yearly sampling periods from patients with respiratory tract infections. The prevalence of β-lactamase-negative ampicillin-susceptible strains was approximately 80% over the sampling period although fewer strains (65·9%) were recovered in the period 1995–1997. TEM-1 type β-lactamase-producing strains were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The BLNAR strains generally continued to be isolated at low frequencies in the 1980s (24,25). However, a surveillance study conducted in Japan in the 1990s showed a marked 19.5% increase in the frequency of BLNAR strains (28). Systematic surveillance studies are essential tools in the effort to define trends in the antimicrobial resistance of bacteria.…”
mentioning
confidence: 99%
“…The BLNAR strains generally continued to be isolated at low frequencies in the 1980s (24,25). However, a surveillance study conducted in Japan in the 1990s showed a marked 19.5% increase in the frequency of BLNAR strains (28). Systematic surveillance studies are essential tools in the effort to define trends in the antimicrobial resistance of bacteria.…”
mentioning
confidence: 99%
“…However, recently, the prevalence of BLNAR strains has been increasing in Japan. 1,2 In Japanese children especially, the frequency of isolation of BLNAR strains has increased rapidly, from 12.7% to 22.1% in 4 years. 11 Recent publications from Japan without genotyping analysis have shown the frequency of isolation of BLNAR to be 9.6%, 12 14.5%, 13 23.1%, 14 and 25.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Although the bacterium is usually sensitive to beta-lactams, betalactamase-negative ampicillin-resistant (BLNAR) strains have been increasing recently in Japan. 1,2 Especially in children, the frequency of isolation of BLNAR strains is rapidly increasing, and problems caused by BLNAR strains are frequently emerging in Japan. 3,4 BLNAR strains acquire drug resistance by mutations in the fts I gene encoding penicillin-binding protein (PBP) 3, which is associated with septal peptidoglycan synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Faropenem exhibited an MIC of 4 g/ml against the BLNAR isolates. Although BLNAR isolates have been emerging in Japan (16,18) and have been isolated from the nasopharynxes of Japanese children with AOM (17), they have remained rare in the United States and among the MEF isolates of H. influenzae collected from children in Israel and Costa Rica in this study (0.5% in both countries). Although all of the H. influenzae isolates from both countries were susceptible to the macrolide azithromycin, there were two isolates of H. influenzae from Costa Rica that were nonsusceptible to the ketolide telithromycin.…”
mentioning
confidence: 82%